2018
DOI: 10.1177/1553350617752263
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Laser Metastasectomy by 1318-nm Neodymium-Doped Yttrium-Aluminum Garnet Laser: A Retrospective Study About Laser Metastasectomy of the Lung

Abstract: Our results show that laser resection of lung metastases can achieve good result, in terms of radical resection and survival, as conventional surgical metastasectomy. The great advantage is the possibility of limiting the damage to the lung. Stapler resection of a high number of metastases would mutilate the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…According to many authors, there is no need to secure the lung parenchyma with clips or other sealants in the case of removing single small lesions with a laser [ 40 ]. Moreover, laser-assisted surgery seems to be a safe and effective alternative to lobectomy in cases of large or central metastases where the SWR is technically impossible and mechanical resection can cause deformation and distortion of the lung parenchyma [ 17 , 18 , 19 , 41 , 42 , 43 ]. Studies have found that the Nd:YAG laser (1318 nm) is a tool that cuts, coagulates, seals, and stops bleeding as well as sterilizing wound edges in an area of up to 5 mm, which may improve the oncological radicality of the resection [ 17 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to many authors, there is no need to secure the lung parenchyma with clips or other sealants in the case of removing single small lesions with a laser [ 40 ]. Moreover, laser-assisted surgery seems to be a safe and effective alternative to lobectomy in cases of large or central metastases where the SWR is technically impossible and mechanical resection can cause deformation and distortion of the lung parenchyma [ 17 , 18 , 19 , 41 , 42 , 43 ]. Studies have found that the Nd:YAG laser (1318 nm) is a tool that cuts, coagulates, seals, and stops bleeding as well as sterilizing wound edges in an area of up to 5 mm, which may improve the oncological radicality of the resection [ 17 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the Nd:YAG laser (1318 nm) is a tool that cuts, coagulates, seals, and stops bleeding as well as sterilizing wound edges in an area of up to 5 mm, which may improve the oncological radicality of the resection [ 17 , 44 , 45 ]. This technique has been positively assessed in terms of its facility, the low percentage of perioperative complications, completeness of resection, and oncological results [ 19 , 41 , 44 , 46 ]. In the retrospective study by Stefani et al (2019), laser-assisted resection of large and centrally located lung masses resulted in a better immediate surgical outcomes and shorter hospital stay, while the recurrence rate and survival times did not differ when compared with lobectomy [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One typical medical application is in the removal of tumor tissues using the 1318-nm high-power laser. [7][8][9][10][11] Other potential applications include nonablative skin rejuvenation treatment and neural stimulation. 12,13 Considering the increasing use of NIR lasers in the wavelength range of 1300 to 1400 nm, [7][8][9][10][11][12][13] it is important that they are used safely and that their use is not unnecessarily restricted.…”
Section: Introductionmentioning
confidence: 99%
“…S o m e i n v e s t i g a t o r s h a v e e m p l o y e d 1 , 3 1 8 -n m neodymium-doped yttrium-aluminum garnet laser for resection of lung metastases. They demonstrated that with the use of this technique achieved good results, in terms of radical resection and survival, as conventional surgical metastasectomy (22).…”
mentioning
confidence: 98%